Our modern banking and monetary system - Thomas, Rollin George (Englewood Cliffs, N.J., Prentice-Hall, 1964)
This edition like its predecessors, is designed to achieve two fundamental purposes: first, to describe the nature and operations of our money and banking systems; second, to apply modern monetary theory and banking theory to present-day domestic and international problems. The book is divided into eight parts. Parts one to Four provide the institutional background for the study of central bank and monetary theory and the problems related to them. Parts Five and Six apply present-day monetary theory to the problem of explaining the supply of money and its demand and the resulting effect upon the level of income, output, and prices. Part Seven deals with the applications of monetary and fiscal policy. Part Eight is devoted to an examination of international monetary relationship with both fixed and flexible exchange rates, the place of the World Bank and the International Monetary Fund, and the gold-exchange standard system of today's world and the balanced-of-payments problems arising from it.
Bibliographical footnotes.
rpm 24/04/2018
Loans
Keywords: Money; Banks and banking; Currency question; Modern banking; Monetary system